Melanism in a Chinese population of Harmonia axyridis (Coleoptera: Coccinellidae): a criterion for male investment with pleiotropic effects on behavior and fertility - Su, Wang; Michaud, J. P.; Xiaoling, Tan; Murray, Leigh; Fan, Zhang (My University, 2013)
In Beijing, China, females of Harmonia axyridis are promiscuous but prefer typical (succinea form) males to melanic ones in the spring generation, ostensibly due to the thermal disadvantages of melanism during summer. We used laboratory observations to test whether males invested differentially in females according to their elytral color, and whether male behavior was phenotype-dependent. Video-recording was used to monitor no-choice mating tests between virgin adults in all phenotype combinations and females were isolated post-copula to observe their egg retention times and reproduction over five days. Females tended to wait longer before using the sperm of melanic males, and melanic females delayed longer than succinic females. Melanic males spent longer in copula with succinic than melanic females and the latter received fewer bouts of male abdominal shaking that correlate with sperm transfer, regardless of the phenotype of their mate. Although melanic males abandoned melanic females faster than did succinic males, they remained in copula with females of both phenotypes for a longer period after shaking, suggesting a larger investment in mate guarding by the less-preferred male phenotype. Although female fecundity did not vary among phenotype combinations, egg fertility was lower for females mated to melanic males, suggesting a pleiotropic effect of melanism on male fertility in addition to its effects on male mating behavior.
Citation: Su, W., Michaud, J. P., Xiaoling, T., Murray, L., & Fan, Z. (2013). Melanism in a Chinese population of Harmonia axyridis (Coleoptera: Coccinellidae): A criterion for male investment with pleiotropic effects on behavior and fertility. Retrieved from http://krex.ksu.edu
Keywords: Male mate choice; Mate guarding; Pleiotropy; Reproductive investment